TREATMENT OF THE T3—4N0M0 BREAST CANCER - K. V. Maximov; I. V. Visotzkaya; V. D. Yermilova; V. P. Letyagin; Ye. M. Pogodina; G. Yu. Chemeris; A. D. Zikiryakhodzhayev; Ye. A. Kim; G. V. Martinova (Опухоли женской репродуктивной системы, 2014)
The aim of the study was to determine the most effective regimens of the neo- and adjuvant therapy of the primary breast cancer of the T3—4N0M0 stages. The data of the clinical observations of the 145 patients with the locally advanced T3—4N0M0 breast cancer, who underwent treatment in the N.N.Blokhin CRC over the period of 1998—2003, were used in the study. The mean age of the patients was 55,3±12,9 years (from 19 to 83 years, median-55 years). The duration of the observation of the patients was 46,5±28,51 months (from 3,6 to 109,4 months, median-44,5 months). For patients with the breast cancer of the T3—4N0M0 stages combined treatment modality was implemented with the use of neo- and adjuvant therapy in all the cases.